New estimates of public employment and training program net impacts: a nonexperimental evaluation of the workforce investment act program - Carolyn J. Heinrich; Peter R. Mueser; Kenneth R. Troske; Kyung-seong Jeon; Daver C. Kahvecioglu (Institute for the Study of Labor (IZA), 2009)
This paper presents nonexperimental net impact estimates for the Adult and Dislocated Worker programs under the Workforce Investment Act (WIA), the primary federal job training program in the U.S, based on administrative data from 12 states, covering approximately 160,000 WIA participants and nearly 3 million comparison group members. The key measure of interest is the difference in average quarterly earnings or employment attributable to WIA program participation for those who participate, estimated for up to four years following entry into the program using propensity score matching methods. The results for the average participant in the WIA Adult program show that participating is associated with a several-hundred-dollar increase in quarterly earnings. Adult program participants who obtain training have lower earnings in the months during training and the year after exit than those who don't receive training, but they catch up within 10 quarters, ultimately registering large total gains. The marginal benefits of training exceed, on average, 400 in earnings each quarter three years after program entry. Dislocated Workers experience several quarters for which earnings are depressed relative to comparison group workers after entering WIA, and although their earnings ultimately match or overtake the comparison group, the benefits they obtain are smaller than for those in the Adult program.
Keywords: J24; J48; 330; Nonexperimental program evaluation; workforce investment act; Arbeitsmarktpolitik; Weiterbildung; Berufsbildungspolitik; Wirkungsanalyse; Bildungsertrag; USA